The atherosclerosis profile by coronary CTA compared to the coronary artery calcium score (CACS) in a young symptomatic high-risk population between 19 and 49 years. (14th October 2021) - Plank, F; Beyer, C; Langer, C; Senoner, T; Bleckwenn, S; Widmann, G; Barbieri, F; Friedrich, G; Dichtl, W; Feuchtner, G
Abstract: Background: Whether the coronary artery calcium score (CACS) or coronary CTA should be used in young high-risk adults for screening of coronary artery disease (CAD), is an open debate and data sparse. Aims: To evaluate the coronary atherosclerosis profile by coronary computed tomography angiography (CTA) in a young symptomatic high-risk population (age, 19–49 years) in comparison with the coronary artery calcium score (CACS). Methods and results: 1137 symptomatic high-risk patients between 19–49 years (mean 42.4y; 33.2%females) with suspected CAD who underwent CTA and CACS were assigned into 6 age groups (19–30; 31–35; 36–40; 41–45; 46–47; 48–49y).CTA-analysis included stenosis severity (CADRADS) and high-risk-plaque ("HRP") criteria. Atherosclerosis was more often detected by CTA than by CACS (45% vs. 27%; p<0.001), >50% stenosis in 13.6% and HRP in 17.7%. Prevalence of atherosclerosis was low and not different between CACS and CTA in the youngest (19–30y:5.2% and 6.4%; 30–35y:10.6% and 16%). Above >35 years, atherosclerosis detection by CTA increased (p=0.004, OR: 2.8, 95% CI: 1.45–5.89); and was higher by CTA as compared to CACS (34.9% vs 16.7%; p<0.001). CTA outperformed CACS among all higher age groups >35 years, with an increasing gap towards a superior performance of CTA along with age: Above 35 years, stenosis severity (CADRADS) (p=0.002) and >50% stenosis increased from 2.6% to 12.5% (p<0.001). The rate of HRP increased linearly with age from 6.4% to 26.5%.The distribution of HRP into CACS0 and CACS>0.1AU was similar among all age groups (CACS 0:45.1% had HRP), with an increasing proportion of HRP in CACS>0.1AU with age. 24.9% of CACS 0 patients had CAD by CTA, 4.4% >50% stenosis and 11.5% HRP. Conclusion: Above 35 years of age, CTA outperforms CACS with an increasing power. Between 19 and 35 years, CACS 0 does not reliably rule out CAD and high-risk-plaque; hence for "noRISK100%safety", CTA is superior.(#eachlifematters) Funding Acknowledgement: Type of funding sources: None.